Understanding Employee Performance Through Job Satisfaction and Motivation in Public Hospitals - Ramadhian, Mochamad Arief Rahman; Pringgabayu, Dematria (The International Journal of Business Review (The Jobs Review), 2024)
Purpose— This study examines the influence of job satisfaction and work motivation on employee performance at Regency Regional General Hospital. Healthcare organizations depend on motivated employees to maintain service quality. Understanding how job satisfaction and motivation affect performance is essential for improving workforce management and efficiency.Design/methods/approach –A quantitative research method was used. The study involved 45 hospital employees, selected through saturation sampling. Data were collected using structured questionnaires and analyzed with multiple linear regression in SPSS. Reliability and validity were confirmed through Cronbach’s Alpha and normality tests.Findings–The results show that job satisfaction significantly affects employee performance (t = 2.142, p 0.05). Employees with higher satisfaction levels perform better. In contrast, work motivation does not significantly impact performance (t = 0.674, p 0.05). This suggests that job satisfaction factors such as compensation, career growth, and work environment play a more crucial role than motivation alone.Research implications/limitations—The study highlights the importance of improving job satisfaction in healthcare settings. However, as the study was conducted in one hospital, the findings may not be applicable to other sectors. Future research should compare results across different institutions and industries. Longitudinal studies could also explore how job satisfaction and motivation change over time.Originality/value–This study contributes to human resource management research by showing that job satisfaction is more influential than motivation in improving performance. It supports Maslow’s hierarchy of needs and Herzberg’s Two-Factor Theory, particularly in the public healthcare sector. The findings provide insights for hospital administrators to enhance employee engagement and productivity.